A Multicenter, Cross-Sectional Assessment of Otolaryngology Knowledge Among Primary Care Trainees. (September 2018) - O'Brien, Daniel C.; Squires, Lane D.; Robinson, Aaron D.; Ramadan, Hassan; Diaz, Rodney
Objectives: (1) Identify knowledge deficits in this cohort regarding basic conditions treated by an otolaryngologist. (2) Determine the training needs of these physicians regarding the care of the head and neck patient. Methods: This cross-sectional assessment used a 10-question, multiple-choice assessment administered to medical students and resident physicians at the University of California, Davis, University of California, San Francisco, and University of West Virginia in the departments of emergency medicine, family medicine, internal medicine, and otolaryngology. Results: The otolaryngology cohort scored an average of 93%, while all others scored 56%. There was no statistical difference in the results between fourth-year medical students and non-otolaryngology residents of any year. Only 16% of the primary care providers and students assessed felt comfortable with these conditions, and 86% (321/372) of the respondents desired increased education on these topics. Conclusion: This study identified significant knowledge gaps among non-otolaryngologists in the diagnosis and treatment of basic head and neck conditions. As a specialty, a greater focus should be placed on improving the familiarity of our primary care colleagues on these conditions.